The Longitudinal Effects of Kindergarten Enrollment and Relative Age on Children's Academic Achievement - Dagli, Ummuhan Yesil; Jones, Ithel (SAGE PUBLICATIONS INC, 2013)
Background: Research findings suggest that there may be some academic benefits for those children whose kindergarten enrollment is delayed, and the risk of underachievement seems to be greater for children who are younger when they first enter kindergarten. Although kindergarten enrollment occurs naturally, certain child, family, and childcare factors will likely influence parents' decisions concerning when to enroll their children in kindergarten. Age-of-entry studies have often neglected assignment bias results from those preenrollment factors. In addition, prior research has defined children's relative age outside of the immediate environment, as opposed to conceptualizing relative age within the context where children actually learn. Purpose: This study examined the relationship between early, on-time, or delayed kindergarten enrollment and children's mathematics and reading achievement from kindergarten through third grade. We predicted that the degree to which delayed, on-time, or early enrollment influences children's reading and mathematics achievement depends on those preenrollment factors that potentially create assignment biases and the relative age of each child to his or her classmates. Research Design: The study used the Early Childhood Longitudinal Study, Kindergarten Class of 1998-1999 (ECLS:K). A propensity score stratification model was used to adjust for sample assignment bias resulting from the preenrollment factors. Then, a cross-classified random effects model was applied. Results: Results showed that certain child and family characteristics and parents' perceptions about school readiness were related to when children first enter kindergarten. After controlling for demographic characteristics and propensity scores resulting from pre-enrollment factors, on average, at the beginning of kindergarten, children whose kindergarten enrollment was delayed had the highest scores in reading and mathematics, followed by children who entered kindergarten on time. Yet, in third grade, these differences were negligible. However, children in the delayed group who were also relatively older than their peers outperformed the other groups in third-grade mathematics. Conclusions: The results suggest that the academic success or failure of children whose kindergarten enrollment is delayed, early, or on time depends on sociodemographic factors as well as the ages of the children in the same class (e.g., child's age relative to his or her classmates). Policy discussions about age of kindergarten entry or changing cutoff dates should include consideration of factors that influence parental decision making, as well as a child's age relative to his or her classmates.
Keywords: SCHOOL READINESS; FULL-DAY; CHRONOLOGICAL AGE; ENTRANCE AGE; ENTRY; RETENTION; ETHNICITY; STUDENTS; PROGRAM; GROWTH; Education & Educational Research